Human inborn errors of immunity underlying Talaromyces marneffei infections: a multicenter, retrospective cohort study - Fan, Huifeng; Yang, Zhiyong; Wu, Yuhui; Lu, Xiulan; Li, Tian; Lu, Xuyang; Lu, Gen; He, Liming; Lu, Guoping; Huang, Li (Frontiers in Immunology, 2025)
IntroductionTalaromyces marneffei (T. marneffei) infections in children can occur secondary to inborn errors of immunity (IEIs). We aimed to investigate the clinical and genetic features of T. marneffei infection in Chinese pediatric patients.Materials and methodsWe retrospectively reviewed 18 pediatric patients with IEIs who were diagnosed with T. marneffei infections at five public hospitals in China from January 2015 to January 2023.ResultsThe common clinical features among the patients were fever, cough, and hepatomegaly. The most common severe complications included septic shock, hemophagocytic lymphohistiocytosis (HLH), and acute respiratory distress syndrome (ARDS). Three cases presented with pan-hypogammaglobulinemia, while three other cases showed heightened levels of IgM. Elevated levels of IgE were detected in five cases, and six cases exhibited decreased T lymphocyte absolute counts. Four children were diagnosed with hyperimmunoglobulin M syndrome (HIGM) due to CD40LG mutations, three cases had severe combined immunodeficiency (SCID), and five were diagnosed with hyper-IgE syndrome (HIES). Gain-of-function (GOF) mutations in STAT1 led to STAT1 GOF in four cases. One patient was diagnosed with caspase-recruitment domain (CARD9) deficiency due to a compound mutation in the CARD9 gene, while another patient was confirmed with adenosine deaminase (ADA) deficiency.ConclusionT. marneffei infections in children with IEIs induced severe systemic complications. These children commonly exhibited abnormal immunoglobulin levels in peripheral blood, and underlying IEIs associated with T. marneffei infections have enhanced our understanding of the disease.